Efficacy of IV Paracetamol in Patients with Renal Colic in Emergency Department - Nasar, Asad Ahmad; Ahmad, Ayesha; Saleem, Safa; Bary, Abdul; Sarfraz, Junaid; Amjad, Maliha; Qammar, Bilal (Indus Journal of Bioscience Research, 2024)
Background: Renal colic, characterized by excruciating flank pain radiating to the groin, arises from urinary tract obstruction, triggering prostaglandin production and increased intra-renal pressure. NSAIDs are the first-line analgesics but have limitations in vulnerable populations. Intravenous paracetamol has emerged as a safer alternative with rapid analgesic effects and fewer adverse outcomes, especially in resource-limited settings. Objective: The objective is to compare the analgesic efficacy of the intravenous paracetamol and intra muscular diclofenac sodium, in the early resolution of pain in acute renal colic. Methods: This randomized controlled trial was conducted from February 2024 to April 2024 at the Emergency Department of Mayo Hospital Lahore. Patients showing clinical signs and symptoms of acute renal colic were randomly assigned to two groups. Group I (n=35) received 1 gram of intravenous paracetamol, while Group II (n=35) was given 50 mg of intramuscular diclofenac sodium. The pain intensity was evaluated using the Verbal Rating Scale (VRS) 30 minutes after treatment. Results: In this study, there were 47 male patients and 23 female patients. The mean age was 38 12 years old. After 30 minutes of administration, the pain relief in the paracetamol group (p value: <0.01) was similar to that of diclofenac group (p value: <0.01). However, the requirement of rescue analgesia was lower in the paracetamol group than diclofenac group. Conclusion: In acute renal colic patients, with the heralded side effects of non-steroidal anti-inflammatory drugs, IV paracetamol is an excellent alternative, with low risk profile and a higher analgesic efficacy.